Psychosocial perspectives among cancer patients during the coronavirus disease 2019 (COVID‐19) crisis: An observational longitudinal study. Issue 5 (18th August 2021) - Turgeman, Ilit; Goshen‐Lago, Tal; Waldhorn, Ithai; Karov, Keren; Groisman, Leora; Reiner Benaim, Anat; Almog, Ronit; Halberthal, Michael; Ben‐Aharon, Irit
Abstract: Background: The coronavirus disease 2019 (COVID‐19) crisis and consequent changes in medical practice have engendered feelings of distress in diverse populations, potentially adversely affecting the psychological well‐being of cancer patients. Aim: The purpose of this observational longitudinal study was to evaluate psychosocial perspectives among patients with cancer on intravenous treatment during the COVID‐19 pandemic. Methods and results: The study recruited 164 cancer patients undergoing intravenous anti‐neoplastic therapy in a tertiary cancer center. Psychosocial indices were assessed at two points in time, corresponding with the beginning of the first wave of COVID‐19 pandemic in Israel (March 2020) and the time of easing of restrictions implemented to curtail spread of infection (May 2020). At Time 1 (T1), elevated COVID‐19 distress levels (score 1 and 2 on 5‐point scale) were observed in 44% of patients, and associated with pre‐existing hypertension and lung disease in multivariate analyses but no demographic or cancer related factors. At Time 2 (T2), 10% had elevated anxiety and 24% depression as indicated by Hospital Anxiety and Depression Scale (HADS‐A/D). COVID‐19 distress at T1 was related to higher levels of HADS‐A at T2 (Spearman 0.33 p < .01), but not HADS‐D. Patients with breast cancer expressed greater COVID‐19 distress compared with other cancer types (p < .01), while both HADS‐A and HADS‐D were highest for patients with GI cancer. Patient report of loneliness and decreased support from relatives were factors associated with HADS‐A (p = .03 and p < .01, respectively), while HADS‐D was not similarly related to the factors evaluated. Conclusion: Patients with cancer undergoing intravenous treatment may be vulnerable to acute adverse psychological ramifications of COVID‐19, specifically exhibiting high levels of anxiety. These appear unrelated to patient age or disease stage. Those with underlying comorbidities, breast cancer or reduced social support may be at higher risk.